Photocatalytic hydrogen generation and CO2 conversion using g-C3N4 decorated dendritic fibrous nanosilica: role of interfaces between silica and g-C3N4 - Rawool, Sushma A.; Samanta, Anupam; Ajithkumar, T. G.; Kar, Yusuf; Polshettiwar, Vivek (ACS Applied Energy Materials, 2020)
We have synthesized g-C3N4 decorated over dendritic fibrous nanosilica (DFNS). The generation of C-N-Si interfaces by coating each fiber of DFNS with g-C3N4 not only provided high surface area but also affected the optical and electronic properties of the composite. The catalyst synthesis reproducibility issue of g-C3N4 was resolved using a vacuum-sealed quartz tube. The extended light absorption in the visible region, enhanced lifetime of photogenerated charge carriers due to the formation of interfaces between silica and g-C3N4 (confirmed by solid-state NMR), and increased surface area result in the improved photocatalytic activity of DFNS/g-C(3)N(4)for hydrogen generation and CO2 conversion.
Keywords: CO2 conversion; DFNS; g-C3N4; Hydrogen generation; nanocatalysts; photocatalysts; Solid-state NMR